Thismia cordata (Thismiaceae), a new fairy lantern species from the Brazilian Atlantic Forest - Ferreira Da Silva, Diego; Ríos, Román Carlos; Mordaski Visini Da Cruz, Vinicyus Jorge; Souza, Inti De; Marcelo Alvarenga Braga, João (Phytotaxa, 2022)
A new species of Thismia (Thismiaceae) from the Brazilian Atlantic Forest is described and illustrated. Thismia cordata belongs to T. subg. Ophiomeris sect. Ophiomeris, and is mainly characterized by its flowers zygomorphic with gibbous perianth tube which is densely pilose on the inner surface, annulus surrounded by a prominent star-shaped ornamentation of 6-lobes with apex acute, densely pilose, outer perianth lobes ovate with base cordate, stamens with connective falcate, ovary glabrous, and stigma sharply trilobed, densely pilose. Detailed description, illustrations, notes on distribution, and preliminary conservation assessment are provided below.